2015
DOI: 10.1016/j.bjane.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose levobupivacaine plus fentanyl combination for spinal anesthesia in anorectal surgery

Abstract: spinal saddle block using hyperbaric levobupivacaine with both 12.5 μg and 25 μg fentanyl provided good quality of anesthesia without motor block for anorectal surgery in the prone position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…[10] Studies reported that addition of 25 μg fentanyl to LA improves anesthesia quality and prolongs postoperative analgesia without prolonging the time to void. [11] Inspired by the above findings, we selected 10 mg dose of levobupivacaine and compared it with 10 mg levobupivacaine plus 25 μg fentanyl given intrathecally for spinal block characteristics. Ozyilkan et al [12] compared 2.2 ml of levobupivacaine plain with 10 μg fentanyl or 2.5 μg sufentanil as adjuvant in spinal anesthesia for caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Studies reported that addition of 25 μg fentanyl to LA improves anesthesia quality and prolongs postoperative analgesia without prolonging the time to void. [11] Inspired by the above findings, we selected 10 mg dose of levobupivacaine and compared it with 10 mg levobupivacaine plus 25 μg fentanyl given intrathecally for spinal block characteristics. Ozyilkan et al [12] compared 2.2 ml of levobupivacaine plain with 10 μg fentanyl or 2.5 μg sufentanil as adjuvant in spinal anesthesia for caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Studies reported that addition of 25 μg fentanyl to LA improves anesthesia quality and prolongs postoperative analgesia without prolonging the time to void. [ 17 ] Inspired by the above findings, we selected 10 mg dose of levobupivacaine and compared it with 10 mg levobupivacaine plus 25 μg fentanyl given intrathecally for spinal block characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain is said to be most severe in anorectal surgery and thus, the choice of anesthetic methods in this procedure is crucial to reduce the postoperative pain as well as postoperative complications 3 . Spinal anesthesia for anorectal surgery is a 04 July 2020 popular and commonly used method characterized by rapid onset and offset, easy mobilization and short hospital stay 4 . No matter how skillfully conducted or successful the result, almost all surgical procedures produce tissue trauma and pain.…”
Section: Introductionmentioning
confidence: 99%